2018
DOI: 10.30818/jitu.1.1.1618
|View full text |Cite
|
Sign up to set email alerts
|

Qur’an Memorizers and Internet: Study at Ma’had Khoir-Ul-Kayyis and Ma’had Kutubussittah Babussalam in Makassar

Abstract: The Quran memorization is a highly recommended education in Islam. At the same time the internet has penetrated and become an irremovable part of all fields of human life, including santri life. Some are optimistic, but some are worried about the harm. The present study will discuss on how the internet utilized among Qur'an memorizers, and how it did affect to the achievement of each of them. It is different with the other scholars who have compared different groups of internet user and proposed contradictory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Besides that, O1, O2, O3, and O4 got caught playing games, watching videos, and/or accessing social media, which were not related to the lessons or the achievements of the learning targets. It is in line with a previous study that found students were often tempted to access things that unrelated to their lesson when accessing the internet [8].…”
Section: Subject Matterssupporting
confidence: 92%
See 1 more Smart Citation
“…Besides that, O1, O2, O3, and O4 got caught playing games, watching videos, and/or accessing social media, which were not related to the lessons or the achievements of the learning targets. It is in line with a previous study that found students were often tempted to access things that unrelated to their lesson when accessing the internet [8].…”
Section: Subject Matterssupporting
confidence: 92%
“…Especially if they do not get proper direction from their parents. Without parents' control, some young students are reportedly tempted to access entertainment and social media content that is not related to the lesson, even though when they first opened the internet they intended to learn [8]. The problem is that most parents in Indonesia are ignoring their children's internet access [9], while students who failed in their courses tended to interact less frequently [10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that madrasas are concerned with memorizing the Al-Qur'an especially from the students' Quran memorization activities (Arifin et.al., 2013;Arifin et al, 2015). Meanwhile, Dhahir (2018) examines the activities of memorizing the Quran in pesantrens.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that consider the internet as a distraction, for example, are indicated in a study by Dhahir (2018), which revealed that students obtain higher results when they are not allowed or limited from accessing the internet. Zahro (2016) did a study comparable to this, measuring the intensity of gadget use and its relation with discipline in memorizing the Quran.…”
Section: Introductionmentioning
confidence: 99%